3D Fusion Echocardiography Improves Transoeosphageal LV Assessment - Rajpoot, K; Augustine, D; Basagiannis, C; Noble, J; Becher, H; Leeson, P (2011)
Accurate left ventricular (LV) assessment by transoesophageal echocardiography (TOE) can be clinically important particularly in intensive care or intraoperative settings. Assessment from TOE views is limited by foreshortened imaging planes and mitral valve pathology. Transgastric short-axis (SAX) views allow better alignment but may be limited by patient tolerability or patient-related factors (e.g. post gastric surgery). Fusion of multiple 3D volume datasets is now technically possible and improves LV visualisation from transthoracic windows. We hypothesized that fusion of full 3D TOE volumes would improve LV image quality and allow SAX image reconstruction from the oesophagus with improved image quality vs. transgastric SAX views. © 2011 Springer-Verlag Berlin Heidelberg.